The Effect of Brand Image on Product Purchase Intention with Customer Satisfaction as A Mediation Variable (Study of Semen Gresik Consumer in East Java) - Manggala Muhammad Badar (Jurnal Ilmiah Mahasiswa FEB, 2020)
PT Semen Gresik will continue to develop its product image as a premium product in order to maintain its position as a market leader, this strategy focuses on building a strong brand image and maintaining customer satisfaction to create sustainable purchasing intention. Currently, the national cement demand is unstable and difficult to predict, so it is necessary to evaluate the corelation between these variables. This research conducted to evaluate corelation among brand image, customer satisfaction and purchase intention.The population in this study is the customer of Gresik cement products located in area 1 of East Java which includes the areas of Surabaya, Gresik, Sidoarjo, and Mojokerto. The sampling technique in this study uses non-probability sampling, while the data collection method uses purposive sampling with 3 criteria, namely: 1) agent, retailer or shop, 2) has been a dealer for more than 2 years and 3) meets the criteria as a distributor or shop that active. The results of this study obtained 134 questionnaires, then carried out descriptive analysis and path analysis (path analysis) with data processing program Partial Least Square (PLS). The conclusions of this study are a) the brand image variable has a positive influence on the purchase intention and customer satisfaction variables, b) the customer satisfaction variable has a positive effect on purchase intention, c) customer satisfaction mediates the relasionship between brand image and purchase intention.Key word : brand image, purchase intention , customer satisfaction